Development of the Strategic Framework for Sustainable Development of the Special Economic Zones in ASEAN Economic Community: A Case Study of Savannakhet - Mukdahan - Kantachon Siwapimon; Thavivongse Sriburi (Applied Environmental Research, 2017)
The study proposes a strategic sustainable development (SD) framework for the special economic zones in the ASEAN Economic Community (AEC) by investigating 11 key factors to the success of SD, using the concepts of Strategic Environment Assessment (SEA) and Sustainability Assessment (SA). The key factors are 1) public education, 2) educational system, 3) international SD standard, 4) policy, 5) management structure, 6) environmental management, 7) zoning, 8) expenditure, 9) public participation, 10) public health and 11) local business protection. The study use qualitative methods including a literature review as well as collection of primary data through a semi-structured interview form by face-to-face in-depth interviewing with 56 stakeholders selected through the triangulation and appreciative inquiry techniques. The data were qualitatively analyzed to present opinions, problems, needs and results according to SEA and SA. Using content analysis, an analysis was conducted of the state of SD in the target areas of Mukdahan and Savannakhet special economic zones. A strategic SD framework was designed for use in the AEC region. The study recommends further investigation of key factors to identify those that may be specific to each area.